High-Resolution Diffusion-Weighted Imaging Improves the Diagnostic Accuracy of Dynamic Contrast-Enhanced Sinonasal Magnetic Resonance Imaging. Issue 2 (March 2017) - Wang, Feng; Sha, Yan; Zhao, Menglong; Wan, Hailin; Zhang, Fang; Cheng, Yushu; Tang, Wenlin
Abstract : Object: The aim of the study was to evaluate the incremental value of high-resolution diffusion-weighted imaging and apparent diffusion coefficient (ADC) mapping compared with that of dynamic contrast-enhanced (DCE) sinonasal magnetic resonance imaging (MRI) in the characterization of benign versus malignant sinonasal tumors at 3.0T. Materials and Methods: Ninety-eight patients (61 females, 37 males; mean age, 48 years) with sinonasal lesions who underwent high-resolution DW-MRI and DCE-MRI were included in this study. The lesions were divided into malignant and benign groups on the basis of pathological examination. In total, 58 malignant tumors and 40 benign tumors were evaluated. Apparent diffusion coefficients were acquired with 0 and 1000 s/mm 2 b values. Semiquantitative parameters (time–signal intensity curve [TIC] type, time of peak enhancement within the first 2 minutes [ T peak ], peak percentage enhancement within the first 2 minutes [PEpeak ], the last time point percentage enhancement [PElast ], and the washout percentage-enhancement difference [PEwashout ]) were derived from DCE-MRI. The DCE-MRI parameters and ADCs were included in multivariate models to predict a diagnosis of a benign versus malignant lesion. Results: The accuracy using semiquantitative DCE-MRI parameters alone was 70.4% (0.693 area under the ROC curve, 57.5% sensitivity, 79.3% specificity). Adding absolute ADCs to dynamic contrast-enhanced MR data showed the higher diagnostic accuracy of 85.7% (0.873 area under the ROC curve, 85.0% sensitivity, 86.2% specificity). Moreover, the absolute ADCs differed significantly between the benign (mean [SD] ADC, 1.211 [0.32] × 10 −3 mm 2 /s) and malignant (mean [SD] ADC, 0.702 [0.28] × 10 −3 mm 2 /s) sinonasal tumors ( P < 0.001). In addition, a significant difference was found between the ADC values of malignant and benign lesions in washout enhancement TICs ( t = 7.039, P < 0.001). Conclusions: High-resolution DWI with ADC mapping significantly improved the diagnostic accuracy of dynamic contrast-enhanced sinonasal MRI at 3.0T. In addition, ADC values could distinguish benign lesions from malignant tumors in washout enhancement TICs.